Southwest Research-Extension Center, Field Day 1996 (Kansas Agricultural Experiment Station Research Reports, 1996)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1996; SRP768; crops; tillage; insect control; weed science